APPLICATION OF POETRY WRITING LEARNING EVALUATION USING ACROSTIC TECHNIQUE - SETIAWIBAWA, BAYU; Supriyana, Asep (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates the acrostic technique as a method of formative evaluation in poetry writing learning, addressing the limitations of conventional evaluation which is subjective and focused on the final product. Through a systematic literature review, it was identified that the acrostic technique, which requires the first letter of each line of poetry to form a vertical keyword (e.g., "LOVE" or "NATURE"), offers a structured framework for holistically assessing the creative process. The research results reveal three key findings: (1) Implementation of the formative cycle was successfully integrated into three stages: (a) providing a vertical theme as a guide, (b) drafting with specific feedback per line, and (c) gradual revision based on teacher input; (2) The technique’s effectiveness was proven in overcoming writer’s block, improving diction precision, strengthening theme comprehension, and integrating cognitive, affective, and psychomotor assessment; and (3) Student responses were predominantly positive (85%) because the acrostic structure reduced anxiety and triggered creativity, although 15% of students felt the structural constraints restricted their emotional flow. In other words, the acrostic technique serves as an authentic, objective, and process-oriented formative evaluation instrument, aligning with the assessment for learning principle in the Merdeka Curriculum.